Study the effect of addition Rockwool fibers on the Shielding Radiation for the X-ray of Low Density Polyethylene (LDPE) - Jasim, Shaymaa; Radhi, Wisam; Ramadhan, Riyadh; Shaban, Raed; Abdulla, Muzahim (Journal of natural sciences, life and applied sciences, 2020)
The extinction of X-rays (radiation attenuation) was studied using the low-density samples of polyethylene polymer to which the rockwool fibers powder is added as filled filler. This latter was blended with (weight percent) and with a micro-filler (filler particle) the sizes equal to or less than
Keywords: rock wool; Rockwool fibers; Low Density Polyethylene; Shielding radiation